Effect of Autolyzed Yeast on Performance and Physiological Indices of Broiler Chickens Reared at High Stock Density - Samaneh Ghaseminejad; Smayyeh Salari (پژوهشهای علوم دامی ایران)
Introduction: Exposure of poultry to various environmental stressors, such as vaccination, heat stress, high stocking density, and direct contact with excrement in the litter, can stimulate the stress response, disrupt the body's immunity, and external pathogenic factors introduce to a healthy animal. Therefore, they affect natural growth and production. High stocking density can be stressful and have harmful effects on the performance and safety of broiler chickens. Among the environmental factors, stocking density is an important factor in the production of broiler chickens due to its effects on health, well-being, and performance. Stocking density is defined based on the number of birds per surface unit or the amount of surface for each bird and based on the kilogram of poultry weight per surface unit. Yeasts and yeast products can act as an alternative to antibiotics to promote growth and disease resistance in poultry. Autolyzed yeast consists of ruptured or lysed cells and includes both intracellular and cell wall parts. Autolyzed yeast is usually concentrated or dried by liquid fermentation of Saccharomyces cerevisiae, and after autolysis or hydrolysis catalyzed by exogenous enzymes. In broiler chickens, the effects of prebiotics are partially dependent on the blocking of pathogen-adherent receptor sites, regulation of the immune system, production of antimicrobial molecules by the intestinal microbial community, and changes in the intestinal microbial structure. Materials and Methods: This experiment was carried for 37 days in 3 periods including starter (1-10 days old), grower (11-24 days old) and finisher (37-25 days old) using 520 one-day-old broiler chickens of Ross 308 commercial strain in a completely randomized design based on factorial arrangement 4 x 2 with 5 replicates. Experimental treatments included different levels of autolyzed yeast (0, 0.1, 0.2 and 0.3%) and 2 density levels (10 (normal density) and 16 (high density) bird per square meter). The basal diet used was adjusted based on the requirements of broiler chickens (Ross, 2019). Food and water were provided ad-libitum. Feed intake (FI) and body weight gain (BWG) of birds were recorded and feed conversion ratio (FCR) was calculated. On the 37th day of the experiment, two birds from each replicate were randomly selected and the weight of different parts of the carcass including the weight of gastrointestinal tract, breast, thigh, gizzard, liver, pancreas, and spleen (as a percentage of live body weight) were recorded. Also, at this time, caecal digesta (1 g) from each bird were aseptically transferred into 9 ml of sterile saline solution and serially diluted. Lactobacilli, Coliforms, and E.Coli were grown on Rogosa–Sharpe agar, MacConkey Agar, and Eosin Methylene Blue Agar, respectively. Plates for Lactobacillus were incubated anaerobically for 48 h at 37 °C. Microbial populations for E. coli and Coliforms were counted after aerobic incubation at 37°C for 24 hours. All samples were plated in duplicate. The obtained data were statistically analyzed using SAS statistical software, GLM procedure. Also, comparison of averages was done by Duncan's multi-range test at 5% probability level. Results and Discussion: The results of the experiment showed that feed intake, body weight gain and feed conversion ratio were not affected by the interaction of yeast and density (P>0.05). However, the use of autolyzed yeast significantly reduced the feed intake in the finisher period as well as the whole period of the experiment (P<0.05). Also, birds reared in high density showed significantly less feed intake and weight gain compared to birds reared in normal density in the finisher period and the whole period of the experiment (P<0.05). The feed conversion ratio in birds fed with autolyzed yeast improved significantly compared to the control treatment in the starter period as well as the entire experimental period (P<0.05). Carcass components and cecum microbial population of broilers were not affected by the interaction of yeast and density (P>0.05). Also, birds reared in high density showed less Lactobacillus population in cecum compared to birds reared in normal density (P<0.05). Using levels of 0.2 and 0.3% of autolyzed yeast in the diet caused a significant decrease in the cecum E. coli population compared to the control treatment. Conclusion: The results of the present study showed that although the use of autolyzed yeast in high density conditions could not affect the functional and physiological parameters of the animal, the use of autolyzed yeast improved the feed conversion ratio and reduced the population of E. coli of cecum.